A Stable Biomass‐Derived Hard Carbon Anode for High‐Performance Sodium‐Ion Full Battery. Issue 1 (11th November 2020) - Hu, Hai-Yan; Xiao, Yao; Ling, Wei; Wu, Yuan-Bo; Wang, Ping; Tan, Shuang-Jie; Xu, Yan-Song; Guo, Yu-Jie; Chen, Wan-Ping; Tang, Rui-Ren; Zeng, Xian-Xiang; Yin, Ya-Xia; et al.
Abstract : Hard carbon attracts great attention as an anode material for sodium‐ion batteries (SIBs), due to its high conductivity and environmental benignity. However, the practical applications of hard carbon anodes are largely limited by the poor cycling stability and high cost. Herein, bagasse, one of the most abundant biological wastes, is used as a carbon source to construct hard carbon anodes by high‐temperature thermal decomposition. This special material with moderate surface area exhibits long‐term cycling stability (91.5% retention upon 800 cycles at 1000 mA g −1 ). Remarkably, the full battery delivers high midpoint voltage with 2.9 V and superior initial Coulombic efficiency with 93.1% as well as excellent cycling stability (61% retention upon 300 cycles at 125 mA g −1 ). The concept of turning waste into treasure provides an idea for the design of anode materials for SIBs. Abstract : Bagasse, one of the most abundant biological wastes, is used as a carbon source to construct hard carbon anodes by high‐temperature thermal decomposition, thus achieving the goal of "turning waste into treasure." The anode materials have the advantages of high conductivity, low cost, environmental benignity, and long‐term cycling stability.